1994
DOI: 10.1021/ma00103a024
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Normal Mode Relaxation of Poly(lactone)s in Solution

Abstract: We studied the dielectric normal mode relaxation in dilute and semidilute solutions of poly-(e-caprolactone) (PCL) and poly(d-valerolactone) (PVL) in benzene using narrow distribution samples prepared with an initiator of a lanthanoid complex. The effect of long nonpolar groups separating the polar ester groups on the dielectric behavior was investigated by comparing the present results with those for cis-polyisoprene (PI) solutions reported previously. In dilute solutions, the longest relaxation time r for bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 8 publications
0
29
1
Order By: Relevance
“…14, 16 The deviation of the present data of dilute solution from the Zimm theory can be attributed to a broader distribution of MW than used previously (M w =M n < 1:1). We also note in Figures 1 and 2 that the loss curves broaden with increasing C. Similar behavior was observed previously for semidilute solutions of polyisoprene, poly("-caprolactone), poly-(varelolacton), and poly(DL-lactic acid).…”
contrasting
confidence: 46%
See 3 more Smart Citations
“…14, 16 The deviation of the present data of dilute solution from the Zimm theory can be attributed to a broader distribution of MW than used previously (M w =M n < 1:1). We also note in Figures 1 and 2 that the loss curves broaden with increasing C. Similar behavior was observed previously for semidilute solutions of polyisoprene, poly("-caprolactone), poly-(varelolacton), and poly(DL-lactic acid).…”
contrasting
confidence: 46%
“…The results of Á"=C for PPO and PBO solutions are shown in Figures 7a and 7b, respectively. As observed for solutions of polyisoprene, [12][13][14] poly("-caprolactone), 16 and poly-(lactic acid), 17 the relaxation strength decreases with increasing concentration due to the screening of the excluded volume effect on the chain dimension. The horizontal lines indicate the levels of Á"= of the bulk PPO and PBO where is the bulk density.…”
Section: Relaxation Strengthmentioning
confidence: 74%
See 2 more Smart Citations
“…A similar result was found also for the other type-A polymer, poly(e-caprolactone). [15] From these results, Adachi et al [15] concluded that the model describes the dielectric mode broadening (on the increase of c up to 3c*) and thus the broadening results from changes in the s p /s 1 ratio with c PI . However, the s 2 /s 2,0 and s 3 /s 3,0 ratios increase with c PI more rapidly than the model prediction ( Figure 14 a).…”
Section: Relaxation Timesmentioning
confidence: 98%